2017
DOI: 10.1108/ijpsm-02-2016-0043
|View full text |Cite
|
Sign up to set email alerts
|

How organizational stressors affect collective organizational citizenship behaviors in the French Police

Abstract: Purpose Stress issues are a major concern for public organisations, especially in law enforcement. Organisational context is to blame for high levels of stress and low performance. Thus, the purpose of this paper is twofold. First, the authors aim to understand how one contextual variable – organisational stressors that emanate from the police station’s characteristics – affect organisational citizenship behaviour (OCB). The second research aim is to assess how promoting trust in the police station can help mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 67 publications
0
10
0
1
Order By: Relevance
“…Stressed employees typically interpret their environment through a negative lens (Lang et al, 2011). As stress creates negative emotions (Molines et al, 2017; Schulz et al, 2004), which often characterize relationship conflict (Ren & Gray, 2009; Spector & Fox, 2005), workload should be associated with a higher level of relationship conflict. Consistent with this reasoning, prior research demonstrates that workload often makes it emotionally more difficult for employees to manage their interpersonal relationships with coworkers (Greenglass et al, 2003).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Stressed employees typically interpret their environment through a negative lens (Lang et al, 2011). As stress creates negative emotions (Molines et al, 2017; Schulz et al, 2004), which often characterize relationship conflict (Ren & Gray, 2009; Spector & Fox, 2005), workload should be associated with a higher level of relationship conflict. Consistent with this reasoning, prior research demonstrates that workload often makes it emotionally more difficult for employees to manage their interpersonal relationships with coworkers (Greenglass et al, 2003).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…This means job resources are able to buffer negative effects of job demands. Research has shown that job resources play a particularly important role for employee well-being when job demands are high (Molines, Sanséau, & Adamovic, 2017). Taken together, the JDR model analyzes the interaction of job demands and job resources, and argues that an imbalance has dysfunctional effects on employee well-being and performance.…”
Section: Review Of Research On the Job Demands-resources Modelmentioning
confidence: 99%
“…A new employee-focused HRM [ 17 ] based on job demands-resources model and research about quality of work life [ 18 ] has been emphasized for implementation in recent years mainly by modern human resources management, because only a satisfied employee can create added value and contribute to patient’s satisfaction. The job demands-resources model is focused on the analysis of predictors and conditions of psychological wellbeing and stress in the work environment [ 19 , 20 , 21 , 22 , 23 ]. New findings within the job demands—resources model highlight the proactive role of management on the one hand by continuously monitoring and optimizing job characteristics, communicating vision and providing direction and support.…”
Section: Introductionmentioning
confidence: 99%